“Not Trained, Yet Teaching”: ELL Students’ Identity and Competence Development in Teaching Practicum - Pritz Hutabarat; Sonny Angjaya (Journal of Education and Teaching (JET), 2025)
This study examines the experiences of ELL students regarding their teaching practice and their development of pedagogical competence despite insufficient training.  Conducted as qualitative research, this study gathered data from 36 ELL students via reflective essays, semi-structured interviews, and classroom observations, which were subsequently analyzed thematically.  The results show five main themes: student engagement, classroom management, adaptability, teaching anxiety, and peer support.  These themes reflect challenges encountered by education majors; however, the analysis indicates that ELL students experience them in unique ways due to their disciplinary background.  Specifically, they relied heavily on peer support as an informal community of practice, negotiated teaching anxiety linked to their perceived lack of legitimacy, and shifted from linguistic to pedagogical and finally to adaptive competence during TP.  This study makes a theoretical contribution by introducing the ELL TP Experience Framework, which conceptualizes transformative pedagogy as a process through which students transition from linguistic competence to pedagogical and adaptive competence while negotiating their teacher identity.